Assessing body sensations in children: Intra-rater reliability of assessment and effects of age - Taylor, S.; McLean, B.; Falkmer, Torbjorn; Carey, L.; Girdler, Sonya; Elliott, Catherine; Blair, E. (The College of Occupational Therapists - UK, 2018)
Introduction: This article examines the effect of age and gender on somatosensory capacity for children and adolescents, and provides preliminary normative data and reliability for the SenScreen©Kids, a new standardised measure of touch, wrist position sense and haptic object recognition. Method: A cross-sectional study of 88 typically developing children aged 6–15 years (mean 10.3 years; SD 2.6 years) was used to determine the developmental effects of age and gender on somatosensory capacity. Intra-rater reliability was assessed in 22 of the 88 participants at two time points (mean 8.8 years; SD 2.6 years). Results: Statistically significant differences were observed between age groups for tactile discrimination, wrist position sense and haptic object recognition, but not for touch registration for which all except one participant achieved a maximum score. There was no effect of gender. Three of four SenScreen Kids subtests demonstrated good intra-rater agreement between time points. Conclusions: Somatosensory capacity increased with age for typically developing children aged 6–15 years. Three subtests of the SenScreen Kids demonstrated good intra-rater reliability with typically developing children. Further investigation of reliability is required, and all subtests require psychometric testing with clinical populations.